ANALISIS PENGELOLAAN LINGKUNGAN PABRIK KELAPA SAWIT BATU AMPAR - PT. SMART Tbk. DALAM IMPLEMENTASI INDONESIAN SUSTAINABLE PALM OIL - Hendra Septiawan; - Hariyadi; Machmud Thohari (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2014)
Indonesian Sustainable Palm Oil (ISPO) is a standard system of sustainable palm oil plantations in Indonesia are economically viable, socially viable and environmentally friendly which is compulsory in accordance with the regulations. This study aims to analyze the environmental management performance in palm oil mill Batu Ampar and formulate the performance optimization based on the ISPO requirements. The evaluation shows that the company can meet the 38 indicators related to environmental management with some of the achievements include utilization of renewable energy sources that generate energy by 5.0664 million KWh, amounting to 1,677,615.89 liters of diesel fuel savings, reduction in CO2 emissions by 70.63 Kg / ton CPO, chemical fertilizers worth saving Rp.5.750.080,00 / ha / year. The optimization strategy for continuous improvement which is based on the SWOT analysis include: the selection of accredited laboratories, improve the performance of Waste Water Treatment Plant, planned to construct methane capture, optimizing the utilization of solid waste, optimizing the reduction of hazardous waste, provide input in determining government policy, and training routine related to environmental management to improve the competence of personnel.Keywords: environmental management, optimization, performance, sustainable